The bark and ambrosia beetles (Coleoptera: Curculionidae: Scolytinae and Platypodinae) of American Samoa - Rabaglia, Robert J.; Beaver, Roger A.; Johnson, Andrew J.; Schmaedick, Mark A.; Smith, Sarah M. (Zootaxa, 2020)
A survey of five of the islands of American Samoa was conducted from 2016–2018 utilizing multi-funnel traps baited with ethanol and quercivorol (attractants for xyleborine ambrosia beetles). Specimens of Scolytinae and Platypodinae from this survey, as well as specimens in the American Samoa Community College Collection were identified. A total of 53 species of Scolytinae and two species of Platypodinae are reported. Fourteen species of Scolytinae and one species of Platypodinae are reported as new to American Samoa. The following new synonymy and new combinations are proposed: Xyleborinus artelineatus (Beeson, 1929) (=Xyleborinus cinctipennis (Schedl, 1980) syn. nov.; Ambrosiophilus wilderi (Beeson, 1929) comb. nov. from Ambrosiodmus; Beaverium swezeyi (Beeson, 1929) comb. nov. from Xyleborus; and Debus fallaxoides (Schedl, 1955) comb. nov. from Xyleborus. The distribution on the islands of American Samoa and taxonomic history of each species is provided.